2010
DOI: 10.1111/j.1468-0459.2010.00387.x
|View full text |Cite
|
Sign up to set email alerts
|

A framework for characterizing fluvial sediment fluxes from source to sink in cold environments

Abstract: A framework for characterizing fluvial sediment fluxes from source to sink in cold environments. Geogr. Ann. 92 A (2): 155-176. to better assess the sensitivity of cold environments to environmental change within the context of contemporary and past sediment flux.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
67
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(67 citation statements)
references
References 110 publications
0
67
0
Order By: Relevance
“…Studies on the relationship between catchment hydrologic conditions and glacial sediment transport in polar regions have been concentrated mainly on glaciers located in the Arctic (Nicholas and Sambrook Smith 1998; Orwin and Smart 2004;Strzelecki 2007;Beylich and Kneisel 2009;Rachlewicz 2009;Orwin et al 2010) and focused on the calculation of sediment suspended concentration and dissolved matter in a stream of water. In contrast, measurements of bedload transport in glaciated catchments are limited to only several publications (Østrem 1975;Ashworth and Ferguson 1986;Pearce et al 2003;Bogen and Møen 2003;Kociuba et al 2010Kociuba et al , 2012Janicki 2014, 2015;Kociuba 2016a, b, in press).…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the relationship between catchment hydrologic conditions and glacial sediment transport in polar regions have been concentrated mainly on glaciers located in the Arctic (Nicholas and Sambrook Smith 1998; Orwin and Smart 2004;Strzelecki 2007;Beylich and Kneisel 2009;Rachlewicz 2009;Orwin et al 2010) and focused on the calculation of sediment suspended concentration and dissolved matter in a stream of water. In contrast, measurements of bedload transport in glaciated catchments are limited to only several publications (Østrem 1975;Ashworth and Ferguson 1986;Pearce et al 2003;Bogen and Møen 2003;Kociuba et al 2010Kociuba et al , 2012Janicki 2014, 2015;Kociuba 2016a, b, in press).…”
Section: Introductionmentioning
confidence: 99%
“…The rivers can develop complex multiple channel patterns, often at a transitional stage [10,11,38]. Scarce detailed research also showed the importance of local factors on the spatial distribution, extent, and temporal frequency of streambank erosion, which as a consequence causes problems in the comparison of obtained results [8,13,22,64,71]. According to Palmer et al [72], large variations at individual sites and in annual rates suggest that between the banks, erosion rates may be confounded by the timing and magnitude of discharge events, storage of sediments within the channel system, and the remobilization of eroded material.…”
Section: Discussionmentioning
confidence: 99%
“…During large floods, particularly ablation-precipitation events, total bedload flux was from 59% to 77% [31,34]. The effect of weather and extreme events on the modern development of the relief of the valley floor and channel was also repeatedly emphasised for proglacial rivers [7][8][9]13,17,20,[22][23][24][25]38,[63][64][65][66].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations